2017
DOI: 10.1016/j.snb.2017.04.045
|View full text |Cite
|
Sign up to set email alerts
|

The pyranine-benzalkonium ion pair: A promising fluorescent system for the ratiometric detection of wound pH

Abstract: Pyranine is a non-toxic fluorescent dye, with a broad range of applications in biomedicine where it allows precise ratiometric detection of pH within the physiological pH window. Hereby, the facile synthesis, potentially interesting for commercial applications, of a novel ion pair between pyranine and benzalkonium is described. Benzalkonium, a quaternary ammonium salt with potent antimicrobial properties, makes pyranine sufficiently hydrophobic to allow its incorporation in conventional membranes and commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 31 publications
(33 reference statements)
0
36
0
Order By: Relevance
“…Plotting the same data in logarithmic scale allows the linearization of the calibration in the range from pH 5 to 8. This strong response represents a substantial improvement compared to our previous work (sixfold increase from pH 5.5 to 8.5) . The pH‐dependent emission properties of the pyranine‐labeled APCN membranes can also be distinguished by the naked eye, when illuminated with a white light source (Figure d).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Plotting the same data in logarithmic scale allows the linearization of the calibration in the range from pH 5 to 8. This strong response represents a substantial improvement compared to our previous work (sixfold increase from pH 5.5 to 8.5) . The pH‐dependent emission properties of the pyranine‐labeled APCN membranes can also be distinguished by the naked eye, when illuminated with a white light source (Figure d).…”
mentioning
confidence: 58%
“…Here, the dye's high water solubility and lack of functional groups besides three sulfonic acids groups can lead to severe limitation in terms of leaching. Recently, we demonstrated that the coupling of pyranine with benzalkonium chloride into a water‐insoluble ion pair can solve this problem for a range of pH values . Loading of the ion pair onto a porous support allowed the fabrication of a sensor for wound pH.…”
mentioning
confidence: 99%
“…In the last few years, some temperature and pH sensors have paved the way for a continuous real time wound monitoring by means of wearable devices or materials suitable for integration in commercial dressings [ 120 , 121 , 122 , 126 , 127 ]. Nevertheless, tests on human patients are needed to confirm the reliability of these sensors for practical use.…”
Section: Discussionmentioning
confidence: 99%
“…Panzarasa et al used a pyranine-benzalkonium ion pair incorporated in membranes and wound dressings to detect pH changes in the range 5.5–7.5, however the standard deviation was too high to discriminate pH values that differs for less of about 0.5 pH units [ 127 ].…”
Section: Sensors For Temperature and Phmentioning
confidence: 99%
“…Panzaras et al [194] developed "bandages with a voice" using a pyranine-benzalkonium ion pair loaded into wound dressings that are able to detect pH changes in the range of 5.5-7.5, based on the UV-induced fluorescence color change of a dye. The pH of the healing wound is around pH 5-6, while the pH in chronic wounds fluctuates between 7 and 8, indicating bacterial infection (Figure 9).…”
Section: Smart Nanomaterialsmentioning
confidence: 99%